Study of Cat’s Welfare Kept at Pet Shops in Bekasi West Java - Reza Sofa Hartuti; Mulyadi Adam; Triva Murtina (Universitas Syiah Kuala, 2014)
The aim of this study was to find out correlation between cat’s welfare and caring management in a number of cats kept at p etshops inBekasi from January to February 2013. This study used a questionnaire with ratings based on five aspects of animal welfare (feeding, healthy,comfortable, fear, and normal behavior) and through direct observation. Data was analyzed using Correlation Test Chi Square with 95%confidence interval. The result showed that there is the corelation between animal welfare and caring management of cats at pet shop in Bekasi,West Java.____________________________________________________________________________________________________________________Key words: animal welfare, cats, pet shops